2014
DOI: 10.1016/j.yebeh.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain complex network analysis by means of resting state fMRI and graph analysis: Will it be helpful in clinical epilepsy?

Abstract: Functional magnetic resonance imaging (fMRI) has just completed 20 years of existence. It currently serves as a research tool in a broad range of human brain studies in normal and pathological conditions, as is the case of epilepsy. To date, most fMRI studies aimed at characterizing brain activity in response to various active paradigms. More recently, a number of strategies have been used to characterize the low-frequency oscillations of the ongoing fMRI signals when individuals are at rest. These datasets ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 70 publications
0
37
0
5
Order By: Relevance
“…5 Network-based approaches have been proposed to determine the pathophysiologic organization of the seizure-prone state in epilepsy, 6 and complex networks become of major interest in the epilepsy research with the advent of novel imaging and recording technologies allowing the analysis of high-resolution structural and functional data in the last ten years. 7 Alongside these developments, an increasing number of studies have demonstrated that JME is regarded as a disruption of structural and functional networks, and it can significantly contribute to the understandings of JME pathogenesis. However, most of the previous studies have shared the problem of enrolling heterogeneous groups, thereby mixing patients with newly diagnosed epilepsy and chronic epilepsy.…”
mentioning
confidence: 99%
“…5 Network-based approaches have been proposed to determine the pathophysiologic organization of the seizure-prone state in epilepsy, 6 and complex networks become of major interest in the epilepsy research with the advent of novel imaging and recording technologies allowing the analysis of high-resolution structural and functional data in the last ten years. 7 Alongside these developments, an increasing number of studies have demonstrated that JME is regarded as a disruption of structural and functional networks, and it can significantly contribute to the understandings of JME pathogenesis. However, most of the previous studies have shared the problem of enrolling heterogeneous groups, thereby mixing patients with newly diagnosed epilepsy and chronic epilepsy.…”
mentioning
confidence: 99%
“…This method have become a great tool in the field of technological, biological and amusing sciences such as the science of ecological networks, the World Wide Web, amusing networks and neuroscience. Onias et al (2014) described that a network is a way to code a set of elements together with their connections. The elements are identified as nodes and their connections are identified as edges.…”
Section: Graph Based Analysis Of Complex Brain Networkmentioning
confidence: 99%
“…Therefore, the analysis of effective connectivity requires two important concepts; a selection of causal model and model parameter estimation. Common techniques of exploring the effective connectivity includes dynamic causal modeling (DCM) [39,6,13,40,41,42], Granger causal modeling (GCM) [42,43,41,13,44] and structural equation modeling (SEM) [45,46,47,20,48].…”
Section: Effective Connectivitymentioning
confidence: 99%